Perencanaan Tata Penguat Bunyi, GKE Imanuel Muara Teweh - Frengky Benediktus Ola (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Church worship spaces are acoustic spaces that require clear sound transmission to support liturgical functions. In many churches, including GKE Imanuel Muara Teweh, natural acoustic conditions and inappropriate loudspeaker (LS) arrangements result in uneven sound distribution, high reverberation time, and low intelligibility. This study aims to evaluate the existing condition of the LS layout and formulate improvement recommendations based on quantitative analysis and simulation using EASE FOCUS 5 software. The study was conducted through mapping of SPL distribution, stereo balance, SPL range, and SPL differences at mid-frequency, accompanied by community participation methods for the decision-making process. The analysis results show that the existing condition has significant sound unevenness with an SPL range of up to 18 dB and a difference in conversational frequencies >6 dB, thus disrupting comfort and hearing clarity. Three LS layout recommendations were simulated: (1) optimization of the existing LS, (2) addition of an 8” LS, and (3) addition of a 15” LS and an 8” LS. Recommendation 3 provided the best results with the most even sound distribution, an SPL range of only 7 dB, and much better sound balance, especially in the wing area. However, this recommendation requires a higher investment cost than the other two options. The results of this study serve as a basis for the church building committee to determine the implementable design by considering the desired acoustic quality and budget availability.